Rapid 3D phenotyping of chick embryo liver development at HH22-HH41 embryonic stages using X-ray microcomputed tomography with PTA staining - Igor Rzhepakovsky; Sergei Piskov; Svetlana Avanesyan; Marina Sizonenko; Lyudmila Timchenko; Magomed Shakhbanov; Gloria Nassali; Idrisa Kiryowa; Andrey Nagdalian (PLoS ONE, 2025)
Animal models, particularly the chicken embryo (CE), remain crucial for advancing developmental biology and medicine. Liver embryogenesis, a complex and tightly regulated process, is particularly susceptible to developmental abnormalities. This study presents a comprehensive 2D and 3D µCT analysis of CE liver development (HH22–HH41) using a refined 1% phosphotungstic acid (PTA) staining protocol. Our methodology yielded high-resolution visualization of liver microstructures, including intricate vascular networks, with image quality and contrast comparable to histological analysis. Quantitative assessment revealed a critical period of rapid liver growth between incubation days 6 and 9 (HH29–HH35), followed by the stabilization of hepatic vascular volume by day 10 (HH36). The ease of structural orientation in µCT datasets, enhanced by 3D renderings, further underscores the technique’s utility. By establishing µCT as an effective tool for liver imaging, this study provides essential normative data on the liver’s spatial organization, morphology, and vascular architecture during embryogenesis, thereby opening new avenues for research in embryology, teratology, pharmacology, and toxicology.